Manajemen Krisis dalam Mempertahankan Kepercayaan Publik pada Lembaga Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
Public trust constitutes a strategic asset for the sustainability of Islamic educational institutions, yet it may deteriorate when institutions fail to respond appropriately to crises. Service-related problems, internal conflicts, limited transparency, and the spread of negative information can develop into legitimacy crises when they are not managed systematically. This study aims to analyze crisis management as a strategy for maintaining public trust in Islamic educational institutions. A qualitative approach was employed using a literature review method. Data were drawn from scholarly journal articles, academic books, previous research findings, and relevant documents, which were analyzed through qualitative content analysis and conceptual synthesis. The findings reveal two main insights. First, sustaining public trust requires institutional crisis-management capacity characterized by preparedness, structured response mechanisms, coordination, and accurate and transparent communication. Second, trust recovery requires corrective actions, accountability, and organizational learning capable of transforming crisis experiences into institutional improvements. These findings indicate that crisis management should not be viewed merely as a communication strategy implemented when problems emerge, but as a governance capacity closely associated with institutional legitimacy, organizational resilience, and sustainability. This study contributes to the development of Islamic educational management by positioning public trust as an outcome of governance quality and crisis management as a strategic mechanism for sustaining institutional legitimacy.